Pengembangan Media Pembelajaran Pop-Up Book Etnomatematika Untuk Meningkatkan Kemampuan Literasi Numerasi Siswa - Trisha Hana Maulidya; Adi Mulyono; Aqilah Balqis Safitri; Mufliha Dzahabiyyah; Rika Rahmawati; Arfatin Nurrahmah, M.Pd (Pendidikan Matematika Universitas PGRI Yogyakarta, 2023)
The cause of the low level of education in Indonesia, especially in students' literacy and numeracy skills, is the limited learning media used in schools. The aim of this research is to develop Pop-Up Book-based learning media to improve the literacy and numeracy skills of students at SD Negeri Cisarua 01, Bogor Regency. The ADDIE model consisting of the stages of Analysis, Design, Development, Implementation, and Evaluation is used as a research method. The data analysis technique used is the descriptive analysis technique. The data analyzed includes media suitability data from media experts and material experts as well as responses from students as test subjects. This Pop-Up Book media has a material validity level of 80%, and media validity of 88%. The effectiveness of the Pop-Up Book learning media from the students' pre-test and post-test showed that the value of tcount > ttable (12.786 > 2.056) and was significant 0.000 < 0.05, so Ha was accepted and Ho was rejected. So it can be concluded that there is a significant difference in learning outcomes before and after the application of Pop-Up Book-based learning media in the introduction of plane shapes and space shapes. To see the increase in the calculated Gain Test, the average result obtained was 0.6688 and was in the medium category. Based on the results of the analysis that has been carried out, it can be concluded that the development of Pop-Up Book learning media can improve the numeracy literacy skills of students at SD Negeri Cisarua 01, Bogor Regency. Keywords: Numeracy Literacy Skills, Ethnomathematics, Learning Media, Pop-Up Book.